Liver transplantation outcomes for Australian Aboriginal and Torres Strait Islanders. Issue 7 (July 2014) - Chinnaratha, Mohamed A.; Chelvaratnam, Uthayanan; Stuart, Katherine A.; Strasser, Simone I.; McCaughan, Geoffrey W.; Gow, Paul; Adams, Leon A.; Wigg, Alan J.; on behalf of the Australia and New Zealand Liver Transplant Clinical Study Group
<x xml:space="preserve">Abstract</x> An increased liver disease burden has been reported for Aboriginal and Torres Strait Islanders (ATSIs) in Australia; however, few proceed to liver transplantation (LT). We aimed to compare overall survival and graft survival after LT between ATSI and non‐ATSI populations, assess the factors influencing survival within ATSIs, and finally examine the proportion of ATSIs undergoing LT. This study was a retrospective review of the Australia and New Zealand Liver Transplant Registry from 1985 to 2012 and examined consecutive primary LT performed in Australia. Overall and graft survival were compared between ATSI and non‐ATSI groups. The Accessibility/Remoteness Index of Australia (ARIA) was used to calculate the remoteness of individuals. There were 3493 primary LT performed, and 45 patients (1.3%; 14 children and 31 adults) were ATSIs. The median (range) ages of the ATSI children and adults at the time of LT were 9.6 (0.2‐15.3) years and 44.5 (19.5‐65.5) years, respectively. There were 10 deaths in the ATSI cohort. The median (range) overall survival was similar for ATSI and non‐ATSI children [6.5 (0.1‐23.5) years versus 9.0 (0‐28.2) years, P = 0.9] and adults [7.1 (0.1‐15.7) years versus 6.3 0‐26.7) years, P = 0.8]. The cumulative graft survival was similar for ATSI and non‐ATSI children (P = 0.8) and adults (P = 0.8). High ARIA scores [hazard ratio (HR) = 1.2, 95% confidence interval (CI) = 1.01‐1.53, P = 0.03] in children and blood group O (HR = 3.8, 95% CI = 1.1‐12.7, P = 0.03) in adults predicted worse outcomes for ATSIs. Although ATSIs accounted for 4.7% and 1.8% of the Australian pediatric and adult populations, respectively, they represented only 2.2% of pediatric LT recipients (χ2 = 8.2, P = 0.004) and 1.1% of adult LT recipients (χ2 = 7.9, P = 0.005). In conclusion, overall survival and graft survival after LT are comparable in ATSIs and non‐ATSIs. There is a trend toward increased death/retransplantation in ATSIs from remote areas. ATSI children and adults appear to be underrepresented in the Australian LT population. Liver Transpl 20:798‐806, 2014. © 2014 AASLD.